Investigation And Quantitation Of Phytoconstituents From Oroxylum Indicum Bark By Gc - Mass And Hplc Techniques - PRISCILLA D’MELLO; PREETAM SHETGIRI; KAMIL DARJI. (International Journal of Pharma and Bio Sciences, 2012)
Different types of terpenoids were separated from extract of bark of Oroxylum indicum. The composition of phytoconstituents terpenoids was determined by GC and GC-Mass technique. Sixteen components were identified, out of which three components are major constituents. Identification of all the components was done by spectral studies, retention time and by comparing with standards.